POLITIK PENYETERAAN DAYAH DI ACEH - Al Muhajir (Universitas Islam Negeri Ar-Raniry, 2015)
The relationship between educational institutions and politics is not merely a mutual relationship influence, but also a functional relationship. Institutions and educational processes play important role in structuring the people political behavior in a country or a region. Dayah as the oldest educational institutions in Aceh, which has played a great role, has ups and downs in its legality. After Tsunami and the Helsinki MoU, dayah